A Multisectoral and Collaborative Approach to Stunting Management in South Konawe Regency, Indonesia - Buyung Sarita; Ramadhan Tosepu; Asrip Putera; Isalman (Journal of Health Science and Pharmacy, 2025)
Background: Stunting is a strategic issue in human resource development with a multidimensional nature. In South Konawe Regency, the prevalence of stunting reached 36.6% in 2023, representing a significant increase compared to the previous year. This condition indicates the limited effectiveness of single-sector approaches in efforts to reduce stunting. Objectives: This study aims to explore the effectiveness of a multisectoral and collaborative approach in the management of stunting, particularly through the implementation of social assistance and social protection programs. Methods: This study employed a qualitative approach with a case study design conducted in 13 stunting locus villages across eight sub-districts. Data were collected through in-depth interviews with 39 informants, including village heads, posyandu cadres, midwives, and parents of stunted children, complemented by field observations and document review. Data analysis was carried out through thematic reduction, narrative data presentation, and verification using source and method triangulation. Results: The findings indicate that social assistance and social protection interventions contribute positively to improving household access to nutrition, health services, and family capacity building. However, the effectiveness of program implementation remains constrained by weak intersectoral coordination, inaccuracies in beneficiary data, and low levels of program integration at the village level. Conversely, collaborative practices among local stakeholders particularly community health cadres, village governments, and beneficiary families were identified as key factors in strengthening the stunting management ecosystem. Conclusion: Addressing stunting requires the strengthening of integrated and collaborative governance across sectors, supported by accurate data systems and active community engagement. A sustainable multisectoral approach is a critical prerequisite for enhancing the effectiveness of stunting management at the local level.